Fostering Student Competence in Data Interpretation and Environmental Literacy Through E-PjBL Model Assisted by Computational Simulation - Zul Anwar; Faizul Bayani; Hulyadi (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this research is to identify the effectiveness of the project-based learning model with an environmental issue approach (E-PjBL) model assisted by computational simulation in fostering environmental literacy and data interpretation competence among students. This study is a quantitative descriptive research. The sample consisted of 22 individuals. The research was conducted on students taking general chemistry courses at Mandalika University of Education. The variables studied were environmental literacy and data interpretation competence. Data were collected through descriptive tests. The tests were based on themes and data during the project conducted in the chemistry laboratory of Mandalika University of Education. The data were then described in graphical form and analyzed using the N-Gain test assisted by SPSS 22 application. The results of the E-PjBL assisted by computational simulation proved to increase environmental literacy and data interpretation competence. This statement is supported by the N-Gain test results where 50% of students were in the moderate and high categories, while the rest were in the low category. Based on these findings, it can be concluded that the E-PjBL model assisted by computational simulation is able to improve students' environmental literacy and data interpretation competence.